Incontinentia Pigmenti - BS, G; Pai, GS; Pai, AH; Vinekar, AS; Pai, HS; Noronha, T; Fernandes, MS (Kathmandu University Medical Journal, 2014)
Incontinentia pigmenti is an X- linked dominant condition characterized by cutaneous lesions associated with developmental defects of the eye, skeletal system and central nervous system. We report a case of incontinentia pigmenti in a 30 day old female infant who presented to us with skin eruptions over bilateral upper limbs, lower limbs and trunk since birth. She had linear verrucous plaques and vesicles distributed along the Blaschko’s lines in addition to macular hyperpigmentation in a linear and whorled pattern involving the concerned areas. On ophthalmological examination, proliferative retinopathy in the right eye was noted. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11052 Kathmandu University Medical Journal Vol.11(1) 2013: 91-93